2008
DOI: 10.1002/ajmg.a.32268
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind, parallel, multicenter comparison of L‐acetylcarnitine with placebo on the attention deficit hyperactivity disorder in fragile X syndrome boys

Abstract: Attention deficit hyperactivity disorder (ADHD) is a frequent behavioral problem in young boys with fragile X syndrome (FXS), and its treatment is critical for improving social ability. The short-term efficacy of stimulant medications like methylphenidate (MPH) is well established in children with ADHD. FXS boys treated with MPH have improved attention span and socialization skills; however their mood becomes unstable at higher doses. Therefore, alternative pharmacological treatment of ADHD symptoms is desirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 39 publications
3
60
0
4
Order By: Relevance
“…78,79,80 A doubleblind, parallel, multicentre comparison of L-acetylcarnitine with placebo in patients with attention-deficit/hyperactivity disorder and in boys with fragile X syndrome indicated that L-actylcarnitine significantly improved social behaviour. 81 The alteration in these serum biomarkers could partly contribute to the variety of clinical manifestations of autism. The significant changes in serum pregnanetriol between children with autism and controls indicated perturbations in estrogen metabolism in children with autism.…”
Section: Discussionmentioning
confidence: 99%
“…78,79,80 A doubleblind, parallel, multicentre comparison of L-acetylcarnitine with placebo in patients with attention-deficit/hyperactivity disorder and in boys with fragile X syndrome indicated that L-actylcarnitine significantly improved social behaviour. 81 The alteration in these serum biomarkers could partly contribute to the variety of clinical manifestations of autism. The significant changes in serum pregnanetriol between children with autism and controls indicated perturbations in estrogen metabolism in children with autism.…”
Section: Discussionmentioning
confidence: 99%
“…Acetyl-l-carnitine (Nicetile, a natural compound improving cell metabolism), shown to inhibit cytogenetic expression of the fragile X site in patient-derived cultured lymphocytes (98), was administered to boys with FXS (99). A significant amelioration of the hyperactivity and adaptive behavior of drug-treated boys (compared with those treated with placebo) was observed; however, the methylation state of FMR1 did not change, and the expression of the gene did not increase (100). The third tested compound is valproic acid (101), which is already known as a reactivator of silenced genes (102) that appeared to be a weak reactivator of FM (103).…”
Section: Therapeutic Approaches To Fxsmentioning
confidence: 99%
“…The X chromosome-linked disorder is caused by loss of function of a single gene, fragile X mental retardation 1 (FMR1), most frequently by expansion of CGG repeats (>200 repeats) in the 5Ј regulatory region causing hypermethylation that results in transcriptional silencing (Heitz et al, 1992;Oberle et al, 1991;Pieretti et al, 1991). In addition to mental impairment, FXS patients also display a wide range of social interaction problems characterized by poor eye contact, hyperactivity, attention deficit and obsessive-compulsive behaviors (Boccia and Roberts, 2000;Cornish et al, 2001;Fryns et al, 1984;Torrioli et al, 2008), and hypersensitivity to sensory stimuli (Fryns, 1984;Hessl et al, 2001). Other physical anomalies include elongated face, prominent ears and enlarged male testes (Chudley and Hagerman, 1987;Giangreco et al, 1996;Moore et al, 1982).…”
Section: Introductionmentioning
confidence: 99%